Merenda The History of Sheik Sya'ban in The Framework of Banggai Ethnic Islamic Educational Anthropology 8th Century Ad - Eka Firman Syah; Khozin Khozin; Abdul Haris (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This research was conducted to explore the history of Sheikh Sya'ban in the 8th century AD. The account that will be revealed is how he brought Islam into the midst of the Banggai ethnicity and implemented Islamic education for this ethnicity. Apart from that, this research also aims to contribute to subsequent researchers to create a more in-depth study of Sheikh Sya'ban so that this history can be exposed to light and give birth to new knowledge in the world of education, especially Islamic education. For the problems studied, the researcher used a case study research type with a qualitative approach. From the results of this study, it was found that the implementation of Sheikh Sha'ban's Islamic education for the Banggai ethnic group was: (1) Teaching the basics of Islamic teachings, (2) Guiding them to become preachers, (3) Guiding them to become religious leaders. Meanwhile, the implications of Sheikh Sha'ban's Islamic education can be seen as follows: (1) Creating a predominantly Muslim community, (2) Creating a culture that is acculturated with Islamic religious teachings, (3) Creating a solid Islamic ukhuwah in the Banggai ethnicity.